Identifying Immune Cell Infiltration and Effective Diagnostic Biomarkers in Lung Adenocarcinoma by Comprehensive Bioinformatics Analysis and In Vitro Study - Li, Xinyan; Chen, Xi; Yuan, Yixiao; Zhai, RuiQing; Cho, William C.; Jiang, Xiulin (Frontiers in Oncology, 2022)
Family with sequence similarity 72B (FAM72B) has been characterized in regulate neuronal development. Nevertheless, the prognostic value of FAM72B expression and its function in the immune microenvironment of LUAD currently remains elusive. In this study, by adopting bioinformatics methodology and experimental verification, we found that FAM72B was up-regulated in lung cancer tissues and cell lines, and higher FAM72B level predicted an unfavorable clinical outcome in LUAD patients. Knockdown of FAM72B was significantly inhibited cell proliferation, cell migration, and induced cell apoptosis in LUAD. ROC curve suggested that FAM72B had high predictive accuracy for the outcomes of LUAD. KEGG and GSEA analysis confirmed that FAM72B relative genes were involved in cell proliferation and immune-response signaling pathway. Moreover, up-regulated FAM72B expression was significantly associated with immune cell infiltration in the LUAD tumor microenvironment. Meanwhile, a potential ceRNA network was constructed to identify lncRNA- AL360270.2/TMPO-AS1/AC125807.2/has-let-7a/7b/7c/7e/7f/ FAM72B regulatory axis regulates FAM72B overexpression in LUAD and is associated with poor prognosis. We also confirmed that AL360270.2, TMPO-AS1, and AC125807.2 were significantly up-regulated in LUAD cells lines than human bronchial epithelial cells. In conclusions, FAM72B may serve as a novel biomarker in predicting clinical prognosis and immune status for lung adenocarcinoma.